Murine Extraparenchymal Neurocysticercosis: Appropriate Model for Evaluating Anthelminthic and Anti-Inflammatory Treatment Schedules - Oliveira, Vinícius Tadeu [UNESP] (2024)
Background: Experimental models of neurocysticercosis (NCC) are helpful for an improved understanding of the pathophysiological mechanisms of human diseases and for testing novel therapeutic approaches. Controlling inflammation without reducing the effectiveness of anthelmintics is an important challenge in treating neurocysticercosis. This study investigates the effects of currently used drugs (Albendazole and Dexamethasone) in treating murine extraparenchymal NCC. Methods: Twenty-two rats were inoculated with Taenia crassiceps in the subarachnoid space. The animals underwent magnetic resonance imaging to ascertain the success of infection 3 months after inoculation. The infected animals were randomly assigned to one of the three groups (five rats each): control (no treatment), Albendazole (ABZ), or Albendazole + Dexamethasone (ABZ + DXM) for 14 days. The animals were subsequently euthanised for morphological assessment 2 weeks after the end of treatment. Results: Macroscopically integrated cysts were found in all animals. The ABZ + DXM animals demonstrated lower ventricular sizes, lymphocyte infiltration rates, and immunopositivity for IL-6, with statistical differences in lymphocytes within the arachnoid region. Conclusions: This experimental model, which has previously shown similarities to human infections, is also helpful in reproducing the morphological changes upon treatment with Albendazole and Dexamethasone.